Radiology Education Amid COVID-19 Pandemic and Possible Solutions. Issue 4 (July 2020) - Virarkar, Mayur; Jensen, Corey; Javadi, Sanaz; Saleh, Mohammed; Bhosale, Priya R.
Abstract : Abstract: Along with the rest of the world, the United States is inundated by the COVID-19 pandemic. The medical services in the country have been severely affected. The pandemic poses extraordinary challenges to academic institutions including radiology residency and fellowship programs. Herein, we delineate major difficulties faced by our radiology training program and mitigating countermeasures. The primary objective is to discuss the changes in our radiology training programs due to COVID-19 to allow for continued radiology education.